5-Aminolaevulinic acid dehydratase: metals, mutants and mechanism. (August 2002) - Shoolingin-Jordan, P. M.; Spencer, P.; Sarwar, M.; Erskine, P. E.; Cheung, K.-M.; Cooper, J. B.; Norton, E. B.
Abstract : 5-Aminolaevulinic acid dehydratase catalyses the formation of porphobilinogen from two molecules of 5-aminolaevulinic acid. The studies described highlight the importance of a bivalent metal ion and two active-site lysine residues for the functioning of 5-aminolaevulinic acid dehydratase. Dehydratases fall into two main categories: zinc-dependent enzymes and magnesium-dependent enzymes. Mutations that introduced zinc-binding ligands into a magnesium-dependent enzyme conferred an absolute requirement for zinc. Mutagenesis of lysine residues 247 and 195 in the Escherichia coli enzyme lead to dramatic effects on enzyme activity, with lysine 247 being absolutely essential. Mutation of either lysine 247 or 195 to cysteine, and treatment of the mutant enzyme with 2-bromethylamine, resulted in the recovery of substantial enzyme activity. The effects of the site-directed alkylating inhibitor, 5-chlorolaevulinic acid, and 4, 7-dioxosebacic acid, a putative intermediate analogue, were investigated by X-ray crystallography. These inhibitors reacted with both active-site lysine residues. The role of these two lysine residues in the enzyme mechanism is discussed.